Answer:
4x − 5y = 2
13x − 8y = 26
Explanation:
The equivalent system must have the same solution as the given system of equations:
4x − 5y = 2
3x − y = 8
Here we have that:
y = 3x - 8
4x - 5y = 2
4x - 5(3x - 8) = 2
4x - 15x + 40 = 2
-11x = -38
![x = (38)/(11)](https://img.qammunity.org/2020/formulas/mathematics/college/ls92fop49345pr2to36jlsjbwclwgm4w5q.png)
![y = 3x - 8 = (3*38)/(11) - (88)/(11) = (26)/(11)](https://img.qammunity.org/2020/formulas/mathematics/college/2p1gjf7a2jmzmn5w5ix66jkue99p41jyvz.png)
Now, we have to verify which of these systems have this answer:
4x − 5y = 2
13x − 8y = 4
13x - 8y = 4
![13(38)/(11) - 8(26)/(11) = (286)/(11) \\eq 4](https://img.qammunity.org/2020/formulas/mathematics/college/ftv8wux6e6knbpx41307t6v9qdkswl2ds7.png)
4x − 5y = 2
10x + 3y = 15
10x + 3y = 15
![10(38)/(11) + 3(26)/(11) = (458)/(11) \\eq 15](https://img.qammunity.org/2020/formulas/mathematics/college/u39tppua3trw1j9j41pdtysxh2pvmabl8b.png)
4x − 5y = 2
13x − 8y = 26
4x - 5y = 2
![4(38)/(11) - 5(26)/(11) = (22)/(11) = 2](https://img.qammunity.org/2020/formulas/mathematics/college/wtl7fjf0ewmv680b63cwyvumstiwds3tmv.png)
13x - 8y = 26
![13(38)/(11) - 8(26)/(11) = (286)/(11) = 26](https://img.qammunity.org/2020/formulas/mathematics/college/5w90u6hyqxhg21z9urdyojchc9h07ztf2l.png)
This is the correct answer
So this is the correct answer
4x − 5y = 2
7x + 6y = 10